2021
DOI: 10.3390/ijerph18168274
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and Surgical Treatment of Talar Fractures: A Systematic Review and Meta-Analysis on Clinical Outcomes and Complications

Abstract: The integrity of the talus is crucial for the physiologic function of the feet. The present study sought to summarize the available evidence on clinical outcomes and complications following conservative and surgical treatment of talar fractures. We systematically searched Medline via OVID to find relevant studies with a follow-up of at least six months. Hereafter, the success and complication rates were extracted and analyzed in a random effects proportion meta-analysis. Complications were defined as avascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Increased exposure, sufficient space, and joint locking; these factors are advantageous for the reduction of displaced fracture fragments. For fracture patients, there may be damage to the deltoid ligament complex the tibialis anterior, the tibialis posterior, the flexor hallucis longus, and the flexor digitorum longus [ 3 , 10 ]. Additionally, muscle relaxation under anesthesia can lead to a larger surgical exposure area, which is beneficial for improving the visualization of the fracture fragments [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased exposure, sufficient space, and joint locking; these factors are advantageous for the reduction of displaced fracture fragments. For fracture patients, there may be damage to the deltoid ligament complex the tibialis anterior, the tibialis posterior, the flexor hallucis longus, and the flexor digitorum longus [ 3 , 10 ]. Additionally, muscle relaxation under anesthesia can lead to a larger surgical exposure area, which is beneficial for improving the visualization of the fracture fragments [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The talus is composed of a head, neck, and body, with an extremely irregular shape, and the majority of it is covered by articular cartilage [ 2 ]. Most talar fractures are caused by violent trauma such as falls from height or car accidents [ 3 ]. Furthermore, talar fractures are often associated with ankle fractures, severe soft tissue damage, calcaneal fractures, and metatarsal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Ebraheim et al [ 6 ] demonstrated 38% incidence of AVN after surgical treatment for talar body fractures and Lindvall et al [ 19 ] operatively treated 26 cases of isolated, displaced talar neck and body fractures, reporting that the findings of AVN were seen in 13 cases (50%). Although the incidence of AVN in talar body fractures is reported to vary considerably, many authors agree that the degree of fracture displacement is associated with the incidence of AVN [ 20 ]. However, it has been reported that the incidence of AVN is related to not only the degree of displacement but also poor original blood supply in the talar body and the surgical approach [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, talar fractures are often associated with ankle fractures, severe soft tissue damage, calcaneal fractures, and metatarsal fractures. These can disrupt the ankle joint's mobility system and lead to complications such as ischemic necrosis, arthritis, deformities, etc [3][4][5][6][7]. Therefore, talar fractures should be stabilized, anatomically reduced and rmly xed as early as possible [8,9].…”
Section: Introductionmentioning
confidence: 99%